Pinalatuntunang kagamitang panturo sa aspekto ng pandiwa na nasa aktor-pokus para sa Cebuano mag-aaral sa ikalimang baitang - Loria, Erlinda Espanola 1939- ([Quezon City s.n.], 1972)
This programmed material is designed to teach the different aspects of verbs in the actor-focus to grade five Cebuano learners. It is based on a contrastive analysis of Cebuano and Pilipino to point out the basic similarities and difficulties and to predict the basic sources of difficulties in learning the different aspects of verbs.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Filipino language -- Verb; Filipino language -- Study and teaching -- Cebuano students